The Oncoprotein Tax Binds the SRC-1-Interacting Domain of CBP/p300 To Mediate Transcriptional Activation - Scoggin, Kirsten E. S. (American Society for Microbiology, 2001)
Oncogenesis associated with human T-cell leukemia virus (HTLV) infection is directly linked to the virally encoded transcription factor Tax. To activate HTLV-1 transcription Tax interacts with the cellular protein CREB and the pleiotropic coactivators CBP and p300. While extensively studied, the molecular mechanisms of Tax transcription function and coactivator utilization are not fully understood. Previous studies have focused on Tax binding to the KIX domain of CBP, as this was believed to be the key step in recruiting the coactivator to the HTLV-1 promoter. In this study, we identify a carboxy-terminal region of CBP (and p300) that strongly interacts with Tax and mediates Tax transcription function. Through deletion mutagenesis, we identify amino acids 2003 to 2212 of CBP, which we call carboxy-terminal region 2 (CR2), as the minimal region for Tax interaction. Interestingly, this domain corresponds to the steroid receptor coactivator 1 (SRC-1)-interacting domain of CBP. We show that a double point mutant targeted to one of the putative α-helical motifs in this domain significantly compromises the interaction with Tax. We also characterize the region of Tax responsible for interaction with CR2 and show that the previously identified transactivation domain of Tax (amino acids 312 to 319) participates in CR2 binding. This region of Tax corresponds to a consensus amphipathic helix, and single point mutations targeted to amino acids on the face of this helix abolish interaction with CR2 and dramatically reduce Tax transcription function. Finally, we demonstrate that Tax and SRC-1 bind to CR2 in a mutually exclusive fashion. Together, these studies identify a novel Tax-interacting site on CBP/p300 and extend our understanding of the molecular mechanism of Tax transactivation.